Residential Mobility in Older Dutch Adults : Influence of Later Life Events - Brigitte Bloem; Theo van Tilburg; Fleur Thomése (International Journal of Ageing and Later Life, 2008)
In this study we examined life course events of older Dutch adults in relation to three types of moves and the moving distance. Using the frameworks developed by Litwak and Longino (1987) and Mulder and Hooimeijer (1999), we stipulated life events or triggers and conditions in various life domains. We selected a total of 1,160 men and 1,321 women (aged 54 to 91) from the Longitudinal Aging Study Amsterdam. We conducted multinomial logistic regression analyses to predict moves to a residential care facility, adapted housing or regular housing and to predict the moving distance. Retirement, an empty nest, widowhood and a decline in health each triggered specific moves. In additional analyses, the effects of triggers, especially health changes, were moderated by conditions. There is no indication of a specific trajectory of moves associated with consecutive life events, as suggested by Litwak and Longino. By combining triggers and conditions, however, the framework developed by Mulder and Hooimeijer allows for a more valid analysis.